Perbandingan Sifat Feroelektrik Pada Sintesis Oksida Logam Aurivillius SrBi4Ti4O15 Empat Lapis Dengan Metode Hidrotermal - Karnelasatri, Karnelasatri; Mikrianto, Edi (Indonesian Journal of Chemical Research, 2019)
Aurivillius compounds, SrBi4Ti4O15 (SBT four layers) have been synthesized by hydrothermal method at 200℃ with variation of times 48 hours, 72 hours and 96 hours. Single phase of SrBi4Ti4O15 Aurivillius compounds obtained at the 200 ˚ C, 96 hours and the concentration of NaOH 3M. The Rietica program shown the index Miller result is 1 1 5 1 1 3, 0 2 0, 0 2 4, 2 0 8 2 2 0, 0 2 1 0, 3 1 6, 1 1 1 6 and the space group is A21am with the orthorhombic crystal system. Cell parameters are a = 5.5754 Å, b = 5.5456 Å, c = 41.3642. Ferroelectric properties show the value of remanent polarization Pr (+) and Pr (-) 4,61 C/cm2 and 2,75 C/cm2 and that is much lower than the value of remanent polarization of other material that have been synthesized at 240℃, 72 hours with the same method.